Structural Relationship among Mobile Phone Dependence, Self-Efficacy, Time Management Disposition, and Academic Procras-tination in College Students - PengSheng Chen; Jing Li; Seung-Yong Kim (Tehran University of Medical Sciences, 2021)
Background: We aimed to investigate the relationship among mobile phone dependence, self-efficacy for self-regulated learning, time management disposition, and academic procrastination in Chinese students majoring in physical education. In addition, we explored the mediating roles of self-efficacy for self-regulated learning and time management disposition in the relationship between mobile phone dependence and academic procrastination. Methods: We adopted a random sampling method to identify 324 physical education majors at five universities in Shaanxi Province, China in 2020. Data were analyzed via exploratory factor analysis, confirmatory factor analysis, correlation analysis, structural equation model analysis, and path analysis. Results: Mobile phone dependence had significant positive effects on academic procrastination (P<0.001) and self-efficacy for self-regulated learning (P<0.05) but a significant negative effect on time management disposition (P<0.001). Self-efficacy for self-regulated learning had a significant positive effect on academic procrastination (P<0.001), while time management disposition had a significant negative effect on academic procrastination (P<0.01). Notably, self-efficacy for self-regulated learning and time management disposition mediated the relationship between mobile phone dependence and academic procrastination (P<0.05). Conclusion: In addition to its direct effect on academic procrastination, mobile phone dependence exerts an indirect effect via time management disposition and self-regulated learning efficacy. Reducing students' dependence on mobile phones is necessary for attenuating academic procrastination on university campuses. Thus, universities should aim to restrict the use of mobile phones in the classroom, actively cultivate students' confidence in their self-regulated learning ability, and educate them regarding appropriate time values.